A skills beyond school review of Korea - Kis, Viktoria [Verfasser]; Park, Eunah [Verfasser] (OECD Publishing, 2012)
"Higher level vocational education and training (VET) programmes are facing rapid change and intensifying challenges. What type of training is needed to meet the needs of changing economies? How should the programmes be funded? How should they be linked to academic and university programmes? How can employers and unions be engaged? The country reports in this series look at these and other questions. They form part of 'Skills beyond School', the OECD policy review of postsecondary vocational education and training." This report examines vocational education and training programmes in Korea, covering how they are changing, how they are funded, how they are linked to academic and university programmes and how employers and unions are engaged. (Hrsg., BIBB-Doku)

Table of contents: Chapter 1: Introduction and initial assessment Chapter 2: Mismatches in skills and education Chapter 3: Effective industry engagement in vocational education and training policy making Chapter 4: Quality assurance in junior colleges Chapter 5: Degrees and qualifications Chapter 6: Student choice in postsecondary vocational education and training Chapter 7: Mandatory workplace training in junior college programmes
Keywords: S 1.3 Berufliche Erstausbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.3.4 Asien; Berufsbildungssystem; Berufsbildung; Durchlässigkeit im Bildungssystem; Finanzierung; Südkorea